The Calabrian in the Western Transcaucasian basin (Georgia): Paleomagnetic constraints from the Gurian regional stage - Kirscher, Uwe; Oms, O.; Bruch, A.; Shatilova, I.; Chochishvili, G.; Bachtadse, V. (Pergamon, 2017)
Â© 2017 Elsevier Ltd The precise Eurasian chronostratigraphy of the Neogene-Quaternary period is still hampered by the existence of numerous regional stages often lacking independent and absolute age constraints. Therefore, detailed paleoclimatic reconstructions of areas like the Caucasus are still poorly constrained and the influence of climate variability on faunal interchange between Africa and Eurasia in the late Neogene-Quaternary is still difficult to address. During the last decades, Quaternary sections from western Georgia have produced a wealth of paleoclimatic proxy data. Unfortunately, these sections do not have a robust age control. This is especially true for the Gurian stage which has been vaguely defined as being coeval with the lower Pleistocene on the basis of poorly documented bio- and magnetostratigraphic data. In order to constrain the age of the Gurian stage, a detailed magnetostratigraphic study has been carried out. All major sections with known Gurian sediments in the former Rioni bay (a marine restricted area to the southeast of the Major Caucasus) have been studied. Our results confirm for the first time the strict correlation between the Gurian succession and the Calabrian stage. In addition, our data provides further information on the tectonic setting of the Rioni bay during the Calabrian in this region: (1) in the north, Gurian sediments were unconformably deposited on older Meotian sediments in a piggy back basin, (2) in the south, Gurian sediments are conformably overlying Kujalnician (Plio-Pleistocene) strata, (3) magnetostratigraphic correlation among sections indicate drastic changes in sediment accumulation rates within the basin, (4) rock magnetic experiments reveal significant magnetomineralogical differences between Gurian and the underlying Miocene sediments likely documenting a transition related to changes in oxic conditions, supply of terrigenous material and sedimentation rate close to the Miocene-Pliocene boundary. These results provide a robust basis for further tectonic and paleoclimatic investigations of this region.